Genetic divergence along a climate gradient shapes chemical plasticity of a foundation tree species to both changing climate and herbivore damage - Michael Eisenring; Rebecca J. Best; Mark R. Zierden; Hillary F. Cooper; Madelyn A. Norstrem; Thomas G. Whitham; Kevin Grady; Gerard J. Allan; Richard L. Lindroth (Global Change Biology, 2022)
Climate change is threatening the persistence of many tree species via independent and interactive effects on abiotic and biotic conditions. In addition, changes in temperature, precipitation, and insect attacks can alter the traits of these trees, disrupting communities and ecosystems. For foundation species such as Populus , phytochemical traits are key mechanisms linking trees with their environment and are likely jointly determined by interactive effects of genetic divergence and variable environments throughout their geographic range. Using reciprocal Fremont cottonwood ( Populus fremontii ) common gardens along a steep climatic gradient, we explored how environment (garden climate and simulated herbivore damage) and genetics (tree provenance and genotype) affect both foliar chemical traits and the plasticity of these traits. We found that (1) Constitutive and plastic chemical responses to changes in garden climate and damage varied among defense compounds, structural compounds, and leaf nitrogen. (2) For both defense and structural compounds, plastic responses to different garden climates depended on the climate in which a population or genotype originated. Specifically, trees originating from cool provenances showed higher defense plasticity in response to climate changes than trees from warmer provenances. (3) Trees from cool provenances growing in cool garden conditions expressed the lowest constitutive defense levels but the strongest induced (plastic) defenses in response to damage. (4) The combination of hot garden conditions and simulated herbivory switched the strategy used by these genotypes, increasing constitutive defenses but erasing the capacity for induction after damage. Because Fremont cottonwood chemistry plays a major role in shaping riparian communities and ecosystems, the effects of changes in phytochemical traits can be wide reaching. As the southwestern US is confronted with warming temperatures and insect outbreaks, these results improve our capacity to predict ecosystem consequences of climate change and inform selection of tree genotypes for conservation and restoration purposes.

Root Secondary Metabolites in Populus tremuloides: Effects of Simulated Climate Warming, Defoliation, and Genotype - Zhengzhen Li; Kennedy F. Rubert-Nason; Mary A. Jamieson; Kenneth F. Raffa; Richard L. Lindroth (Journal of Chemical Ecology, 2021)

Genetic variation in aspen phytochemical patterns structures windows of opportunity for gypsy moth larvae - Michael A. Falk; Richard L. Lindroth; Ken Keefover-Ring; Kenneth F. Raffa (Oecologia, 2018)

Experimental climate warming alters aspen and birch phytochemistry and performance traits for an outbreak insect herbivore - Mary A. Jamieson; Ezra G. Schwartzberg; Kenneth F. Raffa; Peter B. Reich; Richard L. Lindroth (Global Change Biology, 2015)
Climate change and insect outbreaks are key factors contributing to regional and global patterns of increased tree mortality. While links between these environmental stressors have been established, our understanding of the mechanisms by which elevated temperature may affect tree–insect interactions is limited. Using a forest warming mesocosm, we investigated the influence of elevated temperature on phytochemistry, tree resistance traits, and insect performance. Specifically, we examined warming effects on forest tent caterpillar ( Malacosoma disstria ) and host trees aspen ( Populus tremuloides ) and birch ( Betula papyrifera ). Trees were grown under one of three temperature treatments (ambient, +1.7 °C, +3.4 °C) in a multiyear open‐air warming experiment. In the third and fourth years of warming (2011, 2012), we assessed foliar nutrients and defense chemistry. Elevated temperatures altered foliar nitrogen, carbohydrates, lignin, and condensed tannins, with differences in responses between species and years. In 2012, we performed bioassays using a common environment approach to evaluate plant‐mediated indirect warming effects on larval performance. Warming resulted in decreased food conversion efficiency and increased consumption, ultimately with minimal effect on larval development and biomass. These changes suggest that insects exhibited compensatory feeding due to reduced host quality. Within the context of observed phytochemical variation, primary metabolites were stronger predictors of insect performance than secondary metabolites. Between‐year differences in phytochemical shifts corresponded with substantially different weather conditions during these two years. By sampling across years within an ecologically realistic and environmentally open setting, our study demonstrates that plant and insect responses to warming can be temporally variable and context dependent. Results indicate that elevated temperatures can alter phytochemistry, tree resistance traits, and herbivore feeding, but that annual weather variability may modulate warming effects leading to uncertain consequences for plant–insect interactions with projected climate change.

Simulated climate warming alters phenological synchrony between an outbreak insect herbivore and host trees - Ezra G. Schwartzberg; Mary A. Jamieson; Kenneth F. Raffa; Peter B. Reich; Rebecca A. Montgomery; Richard L. Lindroth (Oecologia, 2014)

Current known range of the Platte River caddisfly, Ironoquia plattensis, and genetic variability among populations from three Nebraska Rivers - Lindsay A. Vivian; Michael Cavallaro; Kate Kneeland; Erica Lindroth; W. Wyatt Hoback; Kerri M. Farnsworth-Hoback; Robert R. Harms; John E. Foster (Journal of Insect Conservation, 2013)

Qualitative Variation in Proanthocyanidin Composition of Populus Species and Hybrids: Genetics is the Key - Ashley N. Scioneaux; Michael A. Schmidt; Melissa A. Moore; Richard L. Lindroth; Stuart C. Wooley; Ann E. Hagerman (Journal of Chemical Ecology, 2011)

Assimilation exceeds respiration sensitivity to drought: A FLUXNET synthesis - CHRISTOPHER R. SCHWALM; CHRISTOPHER A. WILLIAMS; KEVIN SCHAEFER; ALMUT ARNETH; DAMIEN BONAL; NINA BUCHMANN; JIQUAN CHEN; BEVERLY E. LAW; ANDERS LINDROTH; SEBASTIAAN LUYSSAERT; MARKUS REICHSTEIN; ANDREW D. RICHARDSON (Global Change Biology, 2010)
The intensification of the hydrological cycle, with an observed and modeled increase in drought incidence and severity, underscores the need to quantify drought effects on carbon cycling and the terrestrial sink. FLUXNET, a global network of eddy covariance towers, provides dense data streams of meteorological data, and through flux partitioning and gap filling algorithms, estimates of net ecosystem productivity ( F NEP ), gross ecosystem productivity ( P ), and ecosystem respiration ( R ). We analyzed the functional relationship of these three carbon fluxes relative to evaporative fraction (EF), an index of drought and site water status, using monthly data records from 238 micrometeorological tower sites distributed globally across 11 biomes. The analysis was based on relative anomalies of both EF and carbon fluxes and focused on drought episodes by biome and climatic season. Globally P was ≈50% more sensitive to a drought event than R . Network‐wide drought‐induced decreases in carbon flux averaged −16.6 and −9.3 g C m −2 month −1 for P and R , i.e., drought events induced a net decline in the terrestrial sink. However, in evergreen forests and wetlands drought was coincident with an increase in P or R during parts of the growing season. The most robust relationships between carbon flux and EF occurred during climatic spring for F NEP and in climatic summer for P and R . Upscaling flux sensitivities to a global map showed that spatial patterns for all three carbon fluxes were linked to the distribution of croplands. Agricultural areas exhibited the highest sensitivity whereas the tropical region had minimal sensitivity to drought. Combining gridded flux sensitivities with their uncertainties and the spatial grid of FLUXNET revealed that a more robust quantification of carbon flux response to drought requires additional towers in all biomes of Africa and Asia as well as in the cropland, shrubland, savannah, and wetland biomes globally.

From Genes to Ecosystems: The Genetic Basis of Condensed Tannins and Their Role in Nutrient Regulation in a Populus Model System - Jennifer A. Schweitzer; Michael D. Madritch; Joseph K. Bailey; Carri J. LeRoy; Dylan G. Fischer; Brian J. Rehill; Richard L. Lindroth; Ann E. Hagerman; Stuart C. Wooley; Stephen C. Hart; Thomas G. Whitham (Ecosystems, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Rapid shifts in the chemical composition of aspen forests: an introduced herbivore as an agent of natural selection - Joseph K. Bailey; Jennifer A. Schweitzer; Brian J. Rehill; Duncan J. Irschick; Thomas G. Whitham; Richard L. Lindroth (Biological Invasions, 2007)

Developmental Trajectories in Cottonwood Phytochemistry - Brian J. Rehill; Thomas G. Whitham; Gregory D. Martinsen; Jennifer A. Schweitzer; Joseph K. Bailey; Richard L. Lindroth (Journal of Chemical Ecology, 2006)

A genetic similarity rule determines arthropod community structure - R. K. BANGERT; R. J. TUREK; B. REHILL; G. M. WIMP; J. A. SCHWEITZER; G. J. ALLAN; J. K. BAILEY; G. D. MARTINSEN; P. KEIM; R. L. LINDROTH; T. G. WHITHAM (Molecular Ecology, 2006)
We define a genetic similarity rule that predicts how genetic variation in a dominant plant affects the structure of an arthropod community. This rule applies to hybridizing cottonwood species where plant genetic variation determines plant–animal interactions and structures a dependent community of leaf‐modifying arthropods. Because the associated arthropod community is expected to respond to important plant traits, we also tested whether plant chemical composition is one potential intermediate link between plant genes and arthropod community composition. Two lines of evidence support our genetic similarity rule. First, in a common garden experiment we found that trees with similar genetic compositions had similar chemical compositions and similar arthropod compositions. Second, in a wild population, we found a similar relationship between genetic similarity in cottonwoods and the dependent arthropod community. Field data demonstrate that the relationship between genes and arthropods was also significant when the hybrids were analysed alone, i.e. the pattern is not dependent upon the inclusion of both parental species. Because plant–animal interactions and natural hybridization are common to diverse plant taxa, we suggest that a genetic similarity rule is potentially applicable, and may be extended, to other systems and ecological processes. For example, plants with similar genetic compositions may exhibit similar litter decomposition rates. A corollary to this genetic similarity rule predicts that in systems with low plant genetic variability, the environment will be a stronger factor structuring the dependent community. Our findings argue that the genetic composition of a dominant plant can structure higher order ecological processes, thus placing community and ecosystem ecology within a genetic and evolutionary framework. A genetic similarity rule also has important conservation implications because the loss of genetic diversity in one species, especially dominant or keystone species that define many communities, may cascade to negatively affect the rest of the dependent community.

Genetically based trait in a dominant tree affects ecosystem processes - Jennifer A. Schweitzer; Joseph K. Bailey; Brian J. Rehill; Gregory D. Martinsen; Stephen C. Hart; Richard L. Lindroth; Paul Keim; Thomas G. Whitham (Ecology Letters, 2004)
Fundamental links between genes and ecosystem processes have remained elusive, although they have the potential to place ecosystem sciences within a genetic and evolutionary framework. Utilizing common gardens with cottonwood trees of known genotype, we found that the concentration of condensed tannins is genetically based and is the best predictor of ecosystem‐level processes. Condensed tannin inputs from foliage explained 55–65% of the variation in soil net nitrogen (N) mineralization under both field and laboratory conditions. Alternative associations with litter lignin, soil moisture or soil temperature were relatively poor predictors of litter decomposition and net N mineralization. In contrast to the paradigm that the effects of genes are too diffuse to be important at the ecosystem‐level, here we show that plant genes had strong, immediate effects on ecosystem function via a tight coupling of plant polyphenols to rates of nitrogen cycling.

Productivity overshadows temperature in determining soil and ecosystem respiration across European forests - I. A. Janssens; H. Lankreijer; G. Matteucci; A. S. Kowalski; N. Buchmann; D. Epron; K. Pilegaard; W. Kutsch; B. Longdoz; T. Grünwald; L. Montagnani; S. Dore; et al. (Global Change Biology, 2001)
Summary This paper presents CO 2 flux data from 18 forest ecosystems, studied in the European Union funded EUROFLUX project. Overall, mean annual gross primary productivity (GPP, the total amount of carbon (C) fixed during photosynthesis) of these forests was 1380 ± 330 gC m −2 y −1 (mean ±SD). On average, 80% of GPP was respired by autotrophs and heterotrophs and released back into the atmosphere (total ecosystem respiration, TER = 1100 ± 260 gC m −2 y −1 ). Mean annual soil respiration (SR) was 760 ± 340 gC m −2 y −1 (55% of GPP and 69% of TER). Among the investigated forests, large differences were observed in annual SR and TER that were not correlated with mean annual temperature. However, a significant correlation was observed between annual SR and TER and GPP among the relatively undisturbed forests. On the assumption that (i) root respiration is constrained by the allocation of photosynthates to the roots, which is coupled to productivity, and that (ii) the largest fraction of heterotrophic soil respiration originates from decomposition of young organic matter (leaves, fine roots), whose availability also depends on primary productivity, it is hypothesized that differences in SR among forests are likely to depend more on productivity than on temperature. At sites where soil disturbance has occurred (e.g. ploughing, drainage), soil espiration was a larger component of the ecosystem C budget and deviated from the relationship between annual SR (and TER) and GPP observed among the less‐disturbed forests. At one particular forest, carbon losses from the soil were so large, that in some years the site became a net source of carbon to the atmosphere. Excluding the disturbed sites from the present analysis reduced mean SR to 660 ± 290 gC m −2 y −1 , representing 49% of GPP and 63% of TER in the relatively undisturbed forest ecosystems.

Branch transpiration of pine and spruce scaled to tree and canopy using needle biomass distributions - A.-S. Morén; Anders Lindroth; Jeremy Flower-Ellis; Emil Cienciala; Meelis Mölder (Trees, 2000)

Ubiquitous and tissue-specific gus expression in transgenic roots conferred by six different promoters in one coniferous and three angiosperm species - A. M. Lindroth; R. Grönroos; D. Clapham; J. Svensson; S. von Arnold (Plant Cell Reports, 1999)